Diagnostic workup of acute leukemias of ambiguous lineage. Issue 6 (19th March 2020) - Patel, Sanjay S.; Weinberg, Olga K.
Abstract: Acute leukemias of ambiguous lineage (ALAL) comprise acute undifferentiated leukemias (AUL) and mixed‐phenotype acute leukemias (MPAL). In the revised fourth edition of the World Health Organization (WHO) classification provided further refinements to the diagnostic criteria for ALAL. Molecular characterization of MPALs using comprehensive next‐generation sequencing (NGS) has provided insights into their underlying biology and enabled a deeper understanding of ALAL classification. This review addresses the various components of pathologic assessment to establish a diagnosis of ALAL, and to further subclassify individual cases as AUL or MPAL, with an emphasis on the most up‐to‐date revisions to diagnostic criteria. In addition, key issues related to the detection of minimal residual disease (MRD) in ALALs and MPALs, and recently uncovered novel molecular diagnostic findings that may be helpful in better distinguishing various types of MPALs from each other, and from their "non‐mixed" phenotypic correlates, are also discussed.